STMO-17 Treatment outcome of photodynamic therapy using talaporfin sodium for recurrent high-grade glioma. (6th December 2021) - Ohno, Makoto; Kawauchi, Daisuke; Hayashi, Yoshiharu; Satomi, Kaishi; Miyakita, Yasuji; Takahashi, Masamichi; Yanagisawa, Shunsuke; Tamura, Yukie; Kikuchi, Miyu; Hamada, Akinobu; Narita, Yoshitaka
Abstract: Objective: Photodynamic therapy (PDT) using Talaporfin Sodium (TS) is a novel therapeutic strategy to improve local tumor control in high-grade glioma. TS is a photosensitizer that accumulates in tumor cells and produces highly toxic free radicals by intraoperative irradiation of laser with a 664nm wavelength. However, little is known about the treatment outcomes of PDT in recurrent high-grade gliomas (rHGG). In this study, we investigated the treatment outcome of PDT in rHGG and evaluated the correlation between intratumoral TS accumulation and outcomes. Methods: We included 21 patients with rHGG and 22 tumors, who were treated by PDT between June 2016 and March 2021. TS was transvenously administered 22–26 hours before PDT. Intratumoral TS concentrations were measured by liquid chromatography using frozen tissue. Results: The rHGGs included 10 glioblastoma, IDH1/2-wildtype (GBM, IDH1/2-WT: 45.5%), 3 GBM, IDH1/2-mutant (GBM, IDH1/2-Mut: 13.6%), 7 anaplastic oligodendroglioma, IDH1/2-Mut/codel (AO, IDH1/2-Mut/codel: 31.8%), 1 anaplastic astrocytoma, IDH1/2-WT (AA, IDH1/2-WT: 4.5%), 1 high-grade astrocytoma, IDH1/2-WT (4.5%). The median local progression free survival (PFS) time after PDT was 3.6 months and the median survival time from PDT was 19.4 months. The intratumoral TS concentrations of 7 tumors (TS(-): 31.8%) were below the limit of quantification, and the intratumoral TS concentrations of the remaining 15 tumors (TS(+)) were 43.5 ng/mg-protein (14.7–132 ng/mg-protein). The intratumoral TS concentrations were not significantly associated with IDH1/2 mutation status, cellularity, tumor grade, and pattern of enhancement. The median PFS from PDT tended to be longer in TS(+) than in TS(-) (TS(+): 6.3 vs TS(-): 1.4 months, p = 0.054). Conclusions: We found that the intratumoral TS concentrations were heterogeneous and 31.8% were below the limit of quantification. TS(+) tended to have better local tumor control than TS(-), suggesting the intratumoral TS accumulation have an impact of treatment outcomes of PDT.